Otological and audiological manifestations in cleft lip and cleft palate children: a clinical study - Subramaniam, Vijayalakshmi; S, Manuprasad; Kallikkadan, Hebin H.; K, Vijay Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2015)
Background: Cleft lip and cleft palate are the commonest congenital anomalies of the orofacial region. The incidence of middle ear problems and hearing loss is reported to be higher in children with cleft palate &/or cleft lip. Methods: A prospective, observational case-control study comprising 80 subjects (40 cases and 40 controls) was undertaken at Yenepoya Medical College Hospital, Mangalore, Karnataka, India. All subjects enrolled were subjected to detailed ENT examination including otoscopy, pure tone audiometry and impedance audiometry. Results: Retracted tympanic membrane suggestive of Otitis Media with Effusion (OME) and conductive hearing loss was observed in more than 50% of patients with cleft palate &/or cleft lip. Tympanogram of B type suggesting OME was observed in 27% of cases. Chronic otitis media was observed in 32.5% of cases. Conclusions: The prevalence of OME, Chronic otitis media and hearing loss was observed to be higher among children with cleft palate &/or cleft lip. Otological and audiometric assessment should be performed for all patients having cleft palate &/or cleft lip atleast before surgery in order to facilitate early identification and intervention for middle ear problems particularly middle ear effusion.